Reflections on the Work and Influence of John Maynard Keynes - Smithies, Arthur (Quarterly Journal of Economics, 1951)
I. Introduction, 578. — II. Early beliefs, 579. — III. International proposals 1919–1939, 584. — IV. Domestic proposals 1919–1939, 588. — V. War and postwar proposals, 590. — VI. Appraisal, 593. — VII. Conclusion, 600.